The impact of HIV/AIDS on labor markets, productivity and welfare in Southern Africa: A critical review and analysis - Franklin, S.; Kinkingninhoun-Medagbe, F.M. (2011)
Global estimates of the human immunodeficiency virus (HIV) epidemic as of 2007 shows that about 33million people are living with HIV, the virus that causes acquired immune deficiency syndrome (AIDS).The international labor organization (ILO) estimates that at least 23 million workers in the prime laborforce (aged15 to 49 years) are infected with HIV. More than 70% of the world’s HIV/AIDS infectedpopulation lives in Africa. Within the Africa region, the Southern Africa region has the largest HIVprevalence rate. It is estimated that more than 30% of total world HIV population lives in SouthernAfrica. In this paper, we analyze the extent to which the HIV/AIDS pandemic impacts the labor markets,productivity and welfare in Southern Africa. We hypothesize that the pandemic can reduce the laborforce and productivity, consequently leading to the deterioration in welfare and stagnation of theeconomy. The analysis finds out that a significant proportion of the labor force has been lost to HIV. Inaddition to the loss of workers due to AIDS, the cost of caring for AIDS patients is enormous and hasresulted into the erosion of productivity and profitability in both the formal and informal sectors. Due tothe disproportionate HIV/AIDS prevalence rate between age groups and sex, the pandemic is changingthe age and sex distribution of the labor force. The average age of the labor is declining due to the earlyentry by young and inexperienced people into the labor force. HIV is exerting negative impact onhousehold welfare through the loss of income initially earned by a household member that is a victim ofHIV/AIDS, and that through increased medical expenses by the household on the AIDS victim, most ofthe household income is spent on medication other than other household needs. Some economies inthe region are already facing a reduction in economic growth due to the HIV pandemic and it isobserved that if efforts to prevent its spread are not intensified, such economies would face stagnationat some point.